2013
DOI: 10.1007/s00277-013-1831-0
|View full text |Cite
|
Sign up to set email alerts
|

Cotransplantation of haploidentical hematopoietic and umbilical cord mesenchymal stem cells with a myeloablative regimen for refractory/relapsed hematologic malignancy

Abstract: Human leukocyte antigen haploidentical hematopoietic stem-cell transplantation (haplo-HSCT) is associated with an increased risk of graft failure and severe graft-versus-host disease (GVHD). Mesenchymal stromal cells (MSCs) have been shown to support in vivo normal hematopoiesis and to display potent immunesuppressive effects. We cotransplanted the culture-expanded third-party donor-derived umbilical cord MSCs (UC-MSCs) in 50 people with refractory/relapsed hematologic malignancy undergoing haplo-HSCT with mye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 32 publications
2
47
0
2
Order By: Relevance
“…The probability that patients would attain progression-free survival at 2 years was 66.0 %. Our research indicated that MSCs cotransplantation with HSCs is effective in improving donor engraftment and reducing severe GVHD[149]. Meanwhile, our group observed that Patients with severe AA (n=17) received haploidentical HSCT plus MSCs infusion.…”
mentioning
confidence: 90%
“…The probability that patients would attain progression-free survival at 2 years was 66.0 %. Our research indicated that MSCs cotransplantation with HSCs is effective in improving donor engraftment and reducing severe GVHD[149]. Meanwhile, our group observed that Patients with severe AA (n=17) received haploidentical HSCT plus MSCs infusion.…”
mentioning
confidence: 90%
“…Authors observed no increase in acute or chronic GVHD, with progression-free survival of 66% at 2 years' post-transplant [63]. An additional study is currently accruing at Nanfang Hospital studying the effect of MSCs combined with CB to treat graft failure following autologous stem cell therapy (NCT01763099).…”
Section: Clinical Applications Of Cb/ct-derived Mscsmentioning
confidence: 94%
“…At least eight evaluable papers are available [17][18][19][20][21][22][23][24], with three of them [19,20,23] containing a randomized comparison between an arm of MSCtreated patients and a control arm.…”
Section: Prevention Of Graft-versus-host Diseasementioning
confidence: 99%